2-Aminoethanesulfonic acid: An efficient organocatalyst for green synthesis of spirooxindole dihydroquinazolinones and novel 1, 2-(dihydroquinazolin-3(4H)isonicotinamides in water. Issue 2 (17th January 2020) - Chate, Asha V.; Rudrawar, Priyanka P.; Bondle, Giribala M.; Sangeshetti, Jaiprakash N.
Abstract: A facile and efficient one-pot procedure for the preparation of spirooxindole dihydroquinazolinone derivatives and new N -(4-oxo-2-phenyl-1, 2-dihydroquinazolin-3(4 H )-yl)isonicotinamides from reaction between isatoic anhydride, isoniazid and substituted aldehydes catalyzed by 2-aminoethanesulfonic acid (taurine) is describe. This new protocol has the advantages of environmental friendliness, good yields, and convenient operation. The reaction proceeds efficiently using water as green solvent and nontoxic catalysts that could be efficiently reused. Together with this simple workup procedure, use of the organocatalyst, and water as solvent without the need of column chromatographic purification, are the notable features of this methodology, which make this protocol a very efficient and green alternative to the traditional methods. GRAPHICAL ABSTRACT: